2017
DOI: 10.3389/fcvm.2017.00006
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Concurrent Exercise throughout the Day Does Not Promote Acute Blood Pressure Benefits in Hypertensive Middle-aged Women

Abstract: Hypertension is a chronic disease that affects about 30% of the world’s population, and the physical exercise plays an important role on its non-pharmacological treatment. Anywise, the dose–response of physical exercise fractionation throughout the day demands more investigation, allowing new exercise prescription possibilities. Therefore, this study aimed to analyze the acute blood pressure (BP) kinetics after 1 h of exercises and the BP reactivity after different concurrent exercise (CE) sessions and its fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 60 publications
(57 reference statements)
1
6
0
7
Order By: Relevance
“…Recently, it was reported that the responses of peripheral blood flow and vascular conductance after exercise are not changed between the morning and evening exercise in young subjects, suggesting that the time-of-day effects of exercise on blood pressure and vasodilation are likely reflecting central rather than peripheral regulation (117). Similarly, the higher response of blood pressure to cold exposure in hypertensive adults is reduced by the exercise in the morning but not in the evening (118), suggesting that the morning exercise promotes the reactivity of vasodilation.…”
Section: Blood Pressure and Blood Circulationmentioning
confidence: 99%
“…Recently, it was reported that the responses of peripheral blood flow and vascular conductance after exercise are not changed between the morning and evening exercise in young subjects, suggesting that the time-of-day effects of exercise on blood pressure and vasodilation are likely reflecting central rather than peripheral regulation (117). Similarly, the higher response of blood pressure to cold exposure in hypertensive adults is reduced by the exercise in the morning but not in the evening (118), suggesting that the morning exercise promotes the reactivity of vasodilation.…”
Section: Blood Pressure and Blood Circulationmentioning
confidence: 99%
“…Considerando-se as características da população estudada, a HPE ocorre em hipertensos (AZEVÊDO et al, 2017;CARVALHO et al, 2015;CLÉROUX et al, 1992;FLORAS et al, 1989;HAGBERG;MONTAIN;MARTIN, 1987;LEGRAMANTE et al, 2002;LEHMKUHL et al, 2005;HOGBEN, 2000;RONDON et al, 2002;RUECKERT et al, 1996;SANTAELLA et al, 2006;SOMERS et al, 1991;SOUZA et al, 2016;TAYLOR-TOLBERT et al, 2000;WALLACE et al, 1997;WILCOX et al, 1982), pré-hipertensos (CUNHA et al, 2016;DE BRITO et al, 2015;LACOMBE et al, 2011;LIU et al, 2012) e normotensos (ANGADI; BHAMMAR; GAESSER, 2015;APRILE et al, 2016;BONSU;TERBLANCHE, 2016;COSTA et al, 2016;DANTAS et al, 2017;DUJIĆ et al, 2006;FORJAZ et al, 1998aFORJAZ et al, , 1998bFORJAZ et al, , 2004HALLIWILL;TAYLOR;ECKBERG, 1996;HAMER;BOUTCHER, 2006;HARVEY et al, 2005;HAYES;LUCAS;SHI, 2000;…”
Section: Exercício E Pressão Arterialmentioning
confidence: 99%
“…COSTA et al, 2016;HARVEY et al, 2005;HEFFERNAN et al, 2007) que avaliaram a HPE somente através da comparação entre os valores pós e pré-exercício (cálculo I) e não constataram a ocorrência de HPE, poderiam ter resultados diferentes se tivessem incluído uma sessão controle, pois esses estudos não consideraram que a PA pode aumentar ao longo do tempo. De fato, assim como na presente investigação, outros estudos também verificaram aumento da PA ao longo de sessões controle, especialmente quando essas sessões são realizadas pela manhã e/ou na posição sentada (DE BRITO et al, 2015;FORJAZ et al, 1998b;LACOMBE et al, 2011;TEIXEIRA et al, 2011 GAESSER, 2015;APRILE et al, 2016;AZEVÊDO et al, 2017;BONSU;TERBLANCHE, 2016;CARVALHO et al, 2015;CLÉROUX et al, 1992;COSTA et al, 2016;CUNHA et al, 2016;DANTAS et al, 2017;DE BRITO et al, 2015;DUJIĆ et al, 2006;FLORAS et al, 1989;FORJAZ et al, 1998aFORJAZ et al, , 1998bFORJAZ et al, , 2004HAGBERG;MONTAIN;MARTIN, 1987;HALLIWILL;TAYLOR;ECKBERG, 1996;HAMER;BOUTCHER, 2006;HARVEY et al, 2005;HAYES;LUCAS;SHI, 2000;HEFFERNAN et al, 2007;JONES et al, 2007JONES et al, , 2008…”
Section: Respostas Fisiológicas Ao Exercíciounclassified
See 2 more Smart Citations